Metabolic Profile Correction in Patients with Obstructive Sleep Apnea Depends on the Duration of CPAP Therapy Sessions - M. V. Gorbunova; S. L. Babak; O. Yu. Rebrova; M. A. Karnaushkina; A. G. Malyavin (Архивъ внутренней медицины)
Obstructive sleep apnea (OSA) is a common, heterogeneous chronic disease with sleep fragmentation, metabolic and cardiovascular disorders. Continuous Positive Air Pressure (CPAP) therapy is the primary treatment for patients with OSA. However, the effects of long-term CPAP therapy with night sessions > 6 hours remain poorly understood. The aim of the study was to study the effects of different durations of night sessions of CPAP therapy on the “metabolic profile” of patients with severe OSA. Materials and methods. In a retrospective case-control study comparing two CPAP-therapy regimens by matching pairs from among patients with verified severe OSA (apnea-hypopnea index> 30/h), arterial hypertension, obesity of I-II degrees according to the WHO classification (1997), signed informed consent, 2 groups of 18 people each were formed, comparable in age, anthropometric and somnographic indicators, using CPAP therapy 4-6 hours / night and more than 6 hours / night, respectively. Patients received CPAP therapy for a year, visits were carried out at 3, 6 and 12 months. The severity of sleep apnea was verified during nighttime computed somnography (CSG) on WatchPAT-200 hardware (ItamarMedical, Israel) with original software zzzPATTMSW ver. 5.1.77.7 (ItamarMedical, Israel) by registering the main respiratory polygraphic characteristics from 11.00 PM to 7:30 AM. The optimal therapeutic level of CPAP therapy was titrated at home using devices for automatic selection of therapeutic pressure (PR System One REMstar Auto CPAP Machine with A-Flex (Philips Respironics, USA)) within 7 days after the diagnostic study. To assess the compliance of OSA patients at 3-6-12 months of CPAP-therapy, we used the original compliance analysis program Encore Pro v.2.14 (Philips Respironics, USA). Results. With the initial comparability of the groups, by the 3rd month of therapy, patients with CPAP > 6 h/night showed a statistically significant advantage over the patients with 4-6 h CPAP-therapy in ESS, neck circumference and testosterone. By the 6th month, statistically significant differences of BMI, VAI, leptin, oral glucose tolerance test, fasting insulin, HOMA-IR, lipid metabolism (HDL, LDL, triglycerides, Apo-B) appeared. By the 12th month of therapy, the CPAP group > 6 h/night had a statistically significant advantage in waist circumference, fasting blood glucose and uric acid. Differences between groups at control points persisted throughout the observation period. Conclusions. Long-term home-based CPAP therapy with sessions > 6 h/night has an advantage over therapy with sessions 4-6 h/night in achieving a rapid and pronounced improvement in metabolic profile and hormonal levels in patients with severe OSA.